Anti-inflammatory activity of Haruan (Channa striatus bloch) cream on 12-O-tetradecanoylphorbol-13-acetate-induced chronic dermatitis in mice model - Mohamad Isa, Irma Izani (2015)
Haruan or Channa striatus has been traditionally well-known for its pharmacological benefits in wound healing. Atopic dermatitis or eczema remains a challenge globally due to difficulty in treating the condition, the side effects of corticosteroid-based treatment and the increasing prevalence of the disease worldwide including Malaysia. This research was aimed to discover anti-inflammatory effect of Haruan cream, made from the fish extract on 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced chronic-like dermatitis model on mice ears, by analysing ear oedema, histological findings and gene expression of inflammatory cytokines including TNF-α, IL-1β, IL-10 and IL-4. Briefly,both surfaces of mice ears were applied with 10 μl of TPA (2.5 μg/ 20 μl acetone) for five times on alternate days (day 0, 2, 4, 7 and 9) and with Haruan cream (HC 1%, HC 5% or HC 10%) to the same site twice daily for the last three days of the treatment course (day 7, 8 and 9). When measured on day 8 or 24 hours after the first treatment with Haruan cream, reduction of thickness in mice ear was not statistically significant as compared to negative control. Whereas, when measured on day 10 or 24 hours after the final treatment with Haruan cream, mice ear thickness was significantly reduced (p <0.05) to 0.547 ± 0.025 mm (19.44%) in TPA+HC 1%, 0.556 ± 0.018 mm (18.11%) in TPA+HC 5% and 0.489 ± 0.015 mm (28%) in TPA+HC 10%, in comparison to negative control. Haruan cream also had produced comparable effect as to positive control, hydrocortisone 1% (H-Cort) which has ear thickness of 0.557 ± 0.022 mm or 18% reduction from negative control. Histological comparison had showed evident reduction in various indicators of cutaneous inflammation including dermal oedema, inflammatory cell infiltration and proliferation of epidermal keratinocytes upon treatment with Haruan creams. Gene expression analysis using RT-qPCR method had showed that TNF-α was downregulated from 352.75-fold in negative control to 34.36-fold, 54.19-fold and 112.40-fold in TPA+HC 1%, TPA+HC 5% and TPA+HC 10% groups respectively, with significant reduction (p < 0.05) in both TPA+HC 1% and TPA+HC 5% as compared to negative control. However, there was no significant upregulation of IL-10 by Haruan creams as compared to negative control. Besides, no expression of IL-1β and IL-4 was detected in this animal model of chronic dermatitis. In conclusion, C. striatus is an effective anti-inflammatory agent in this murine phorbol ester-induced chronic dermatitis model, thus suggesting its potential to treat various chronic inflammatory skin diseases including atopic dermatitis.